PERFORMANCE OF EXPERIMENTAL POWER REACTOR COOLING SYSTEM UNDER START-UP CONDITION - Ignatius Djoko Irianto (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2016)
An experimental power reactor has been designed based on high- temperature gas-cooled reactor for experiment purposes. As an experimental reactor, the reactor is able to provide thermal power for various purposes in addition for electricity generation. The reactor is designed to generate 10 MW thermal power from the core cooled by helium gas in the primary cooling system with 700 °C core outlet temperature and cooled by water in the secondary cooling system. The utilization of the thermal energy produced from the reactor is converted to an energy conversion system with a cogeneration configuration. Energy conversion system also serves as a cooling system of the experimental power reactor, which applies indirect cycle. The heat from the primary coolant system is transferred into the secondary coolant system by a heat exchanger acted as a steam generator (SG). The purpose of the paper is to study the performance of the cooling system under start-up condition. Calculation and analysis results related to the thermodynamic parameters and to the cooling system performance are obtained by using CHEMCAD computer code. The calculation shows that if the mass flow rate of the secondary coolant is kept constant at 4.4 kg/second with a constant pressure of 60 bar, the secondary coolant will be entirely in the vapor phase during start-up condition with the the reactor power of 7.5 MW.